Effects of Oral Liposomal Glutathione in Altering the Immune Responses Against Mycobacterium tuberculosis and the Mycobacterium bovis BCG Strain in Individuals With Type 2 Diabetes - To, Kimberly; Cao, Ruoqiong; Yegiazaryan, Aram; Owens, James; Nguyen, Timothy; Sasaninia, Kayvan; Vaughn, Charles; Singh, Mohkam; Truong, Edward; Medina, Albert; Avitia, Edith; Villegas, Jose; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The World Health Organization (WHO) has identified type 2 diabetes (T2DM) as a neglected, important, and re-emerging risk factor for tuberculosis (TB), especially in low and middle-income countries where TB is endemic. In this clinical trial study, oral liposomal glutathione supplementation (L-GSH) or placebo was given to individuals with T2DM to investigate the therapeutic effects of L-GSH supplementation. We report that L-GSH supplementation for 3 months in people with T2DM was able to reduce the levels of oxidative stress in all blood components and prevent depletion of glutathione (GSH) in this population known to be GSH deficient. Additionally, L-GSH supplementation significantly reduced the burden of intracellular mycobacteria within in vitro granulomas generated from peripheral blood mononuclear cells (PBMCs) of T2DM subjects. L-GSH supplementation also increased the levels of Th1-associated cytokines, IFN-γ, TNF-α, and IL-2 and decreased levels of IL-6 and IL-10. In conclusion our studies indicate that oral L-GSH supplementation in individuals with T2DM for three months was able to maintain the levels of GSH, reduce oxidative stress, and diminish mycobacterial burden within in vitro generated granulomas of diabetics. L-GSH supplementation for 3 months in diabetics was also able to modulate the levels of various cytokines.